(untitled) (Experimental biology, 2016)
The research resulted in have been refined and supplemented by existing information on the fauna of aquatic beetles of South Kazakhstan. In generalit was clarified distribution of to 65 species of water beetles belonging to 33 genera of 9 families of 2 suborders. Of these, 6 species are indicated as new to the south of the country or observed in previously unknown habitats.